Granulitos da Região da Várzea do Capivarita Bloco Encruzilhada do Sul, RS - DE LIMA, EVANDRO FERNANDES; PORCHER, CARLOS; WILDNER, WILSON (Pesquisas em Geociências, 1998)
This paper deal with recognition of first granulite occurrence in the eastern portion of the Sul-rio-grandense Shield. The granulitic rocks outcrop in the Varzea do Capivarita region, Encruzilhada do Sul block, as gneisses mostly quartzo-feldspatic with orthopyroxene and biotite, associated with supracrustal rocks metamorphosed under upper amphibolite facies conditions. Microprobe analyses show the orthopyroxene as ferrohypersthene. The mineral assemblage of upper amphibolite facies rocks, such as andulazite + sillimanite + biotite + D-feldpars + quartz, points to low pressure conditions of ca. 4 kb. This high grade association is Brasiliano in age, preserved as roof pendants and megaxenoliths within the younger Brasiliano granitoids. On other side, the Santa Maria Chico Granulites Complex, situated in the western portion of Sul-rio-grandense Shield, formed in higher pressure (9,4 kb) during the Paleoproterozoic.